FAKTOR YANG MEMPENGARUHI CORPORATE INVESTMENT PADA PERUSAHAAN MANUFAKTUR DI BEI - Sheren Lorenzia Kusuma, Yanti (Fakultas Ekonomi, Universitas Tarumanagara, 2020)
Purpose of this thesis is to investigate factors influencing corporate investment of manufacturing companies listed in Indonesia Stick Exchange (IDX). This research done by panel data that have been selected using purposive sampling method for 30 listed manufacturing companies for the periods of 2015-2018. This research used Eviews version 10 software to process the data. The result of research shows that cash flow is not influencing the corporate investment. These results support the pecking order theory that sugest that companies will use internal funding sources first rather than using external funding. Leverage, growth opportunities, cash and liquids, liquidity, and sales are found to have an effect on corporate investment.